PENGARUH INFLASI TERHADAP NILAI TUKAR PETANI DI INDONESIA - Yarham Mulyawan; Fakhruddin Fakhruddin (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis study aims to examine the effect of inflation and regional gross domestic product on exchange rate of farmers in Indonesia. The data in this study used quantitative analysis and panel data regression methods. The data used in this study are quarterly inflation data, regional gross domestic product and farmer exchange rates for 32 provinces in Indonesia. The results from the fixed effect regression model conclude that the probability value of inflation is 0.96 0.05 with a coefficient of -0.01, so that the inflation variable is not significant and has a negative effect on the exchange rate of farmers in Indonesia. The results for gross regional domestic product with a probability value of 0.02 0.05 with a coefficient value of -2.89, so the gross regional domestic product variable is significant and has a negative effect on the exchange rate of farmers in Indonesia. The results of testing the variable Inflation and gross regional domestic product together affect the exchange rate of farmers in Indonesia with the value of Prob. F-statistic 0.00 0.05 and R square of 0.42, this value indicates that the inflation variable and gross regional domestic product affect the exchange rate of farmers in Indonesia.Keywords: Inflation, Gross Regional Domestic Product, Farmers' Exchange Rate.